Métodos históricos utilizados para a resolução de uma equação do segundo grau - Fernandes, Marcos Vinicius Ferreira (Universidade Federal de São Carlos, 2014)
In this work we attempt to answer the question: Can the methods that great mathematicians have used for almost 4 thousand years of history be helpful in the learning process? With a few years of experience in 2nd degree equations, we realize that as soon as the students learn the popular and well-known Bháskara formula (continue...).
Keywords: Matemática - história; Equações de segundo grau; Matemática - ensino; Prática docente; Al-Khwarizmi; History of mathematics; Second degree equation; Mathematics teaching; CIENCIAS EXATAS E DA TERRA